Nuclear receptor co-repressor RIP140 regulates diurnal expression of cytochrome P450 2b10 in mouse liver. (2nd October 2020) - Zhao, Mengjing; Zhao, Huan; Lin, Luomin; Wang, Yi; Chen, Menglin; Wu, Baojian
Abstract: Elucidating the mechanisms for circadian expression of drug-metabolizing enzymes is essential for a better understanding of dosing time-dependent drug metabolism and pharmacokinetics. CYP2B6 (Cyp2b10 in mice) is an important enzyme responsible for metabolism and detoxification of approximately 10% of drugs. Here, we aimed to investigate a potential role of nuclear receptor co-repressor RIP140 in circadian regulation of Cyp2b10 in mice. We first uncovered diurnal rhythmicity in hepatic RIP140 mRNA and protein with peak values at ZT10 (ZT, zeitgeber time). RIP140 ablation up-regulated Cyp2b10 expression and blunted its rhythm in mice and in AML-12 cells. Consistent with a negative regulatory effect, overexpression of RIP140 inhibited Cyp2b10 promoter activity and reduced cellular Cyp2b10 expression. Furthermore, RIP140 suppressed Car- and Pxr-mediated transactivation of Cyp2b10, and the suppressive effects were attenuated when the RIP140 gene was silenced. Chromatin immunoprecipitation assays revealed that recruitment of RIP140 protein to the Cyp2b10 promoter was circadian time-dependent in wild-type mice. More extensive recruitment was observed at ZT10 than at ZT2 consistent with the rhythmic pattern of RIP140 protein. However, the time-dependency of RIP140 recruitment was lost in RIP140 −/− mice. Additionally, we identified a D-box and a RORE cis -element in RIP140 promoter. D-box- and RORE-acting clock components such as Dbp, E4bp4, Rev-erbα/β and Rorα transcriptionally regulated RIP140, potentially accounting for its rhythmic expression. In conclusion, RIP140 regulates diurnal expression of Cyp2b10 in mouse liver through periodical repression of Car- and Pxr-mediated transactivation. This co-regulator-driven mechanism represents a novel source of diurnal rhythmicity in drug-metabolizing enzymes.